Magnitude of episiotomy practice and associated factors among women who gave birth at Hiwot Fana Specialized University Hospital, Eastern Ethiopia - Bekele, Habtamu; Tamiru, Dawit; Debella, Adera; Getachew, Alemeshet; Yohannes, Ephrem; Lami, Magarsa; Negash, Abraham; Asfaw, Henock; Ketema, Indeshaw; Eyeberu, Addis; Habte, Sisay; Eshetu, Bajrond; et al. (Frontiers in Global Women's Health, 2022)
Background Episiotomy is an intentional surgical incision made on the perineum with the aim of enlarging the introits during the second stage of labor or just before delivery of the baby. It sometimes also interferes with the mother's comfort during the postpartum period and has associated complications especially when it is done without indication. However, there is limited information regarding episiotomy practice in the study area. Objective This study aimed to determine the magnitude of episiotomy practice and associated factors among women who gave birth at the Hiwot Fana Specialized University Hospital, Eastern Ethiopia, 2021. Methods A facility-based cross-sectional study was conducted among 408 systematically selected mothers who gave birth at the Hiwot Fana Specialized University Hospital, from 1 January to 30 December 2021. Datas were collected from delivery medical records using a pretested checklist. The extracted data were checked, coded, and entered into the Epi-data version 3.1 and exported to the STATA version 16 software for analysis. Binary logistic regression was fitted to identify factors associated with episiotomy practice. P-values < 0.05 were considered to declare the presence of statistical significance. Results The overall prevalence of episiotomy practice was found to be 43.4 % (95% CI: 38.7, 48.9), and mediolateral was the most commonly practiced episiotomy type (41.4%). Parity [AOR: 6.2; 95% CI (3.8–17.6)], 1st min Apgar score [AOR: 1.6; 95% CI (1.04–2.67)], presence of maternal medical disease [AOR: 3.3; 95% CI (1.09–6.9)], and induced labor [AOR: 1.6; 95%CI (1.12, 4.13)] were significantly associated with the episiotomy practice. Conclusion The prevalence of episiotomy practice in the study area was high. Parity, presence of maternal medical disease, induction of labor, and 1st min APGAR score were significant factors associated with episiotomy practice. Considering the presence of appropriate indications or preventing unjustifiable indications, can help to reduce the current high practice rates.